Planet Earth : finding balance on the blue marble with environmental science activities for kids - Reilly, Kathleen M. ("Build it yourself" series., 2019)
Provides middle grade students with information on all aspects of the natural world including the solar system, the atmosphere, Earth, pollution, climate change, and recycling. Includes hands-on STEM activities, fact boxes, links to online primary sources, real-life environmental connections, a glossary, critical thinking questions, a timeline, and color photographs.